Results of surgical treatment of patients, suffering hepatic cirrhosis and cholestatic syndrome - О. F. Dzygal; І. М. Deykalo (Клінічна хірургія, 2018)
Objective. Determination of the surgical treatment efficacy in patients, suffering hepatic cirrhosis (HC), in presence of cholestatic syndrome (CHS).